Change of Direction Deficit: A More Isolated Measure of Change of Direction Performance Than Total 505 Time. Issue 11 (November 2016) - Nimphius, Sophia; Callaghan, Samuel J.; Spiteri, Tania; Lockie, Robert G.
Abstract : Abstract: Nimphius, S, Callaghan, SJ, Spiteri, T, and Lockie, RG. Change of direction deficit: A more isolated measure of change of direction performance than total 505 time. J Strength Cond Res 30 (11): 3024–3032, 2016—Most change of direction (COD) tests use total time to evaluate COD performance. This makes it difficult to identify COD ability because the majority of time is a function of linear running. The COD deficit has been proposed as a practical measure to isolate COD ability independent of sprint speed. This study evaluated relationships between sprint time, 505 time, and COD deficit, and whether the COD deficit identified a different and more isolated measure of COD ability compared with 505 time. Seventeen cricketers performed the 505 for both left and right sides and 30-m sprint tests (with 10-m split time). The COD deficit for both sides was calculated as the difference between average 505 and 10-m time. Correlations were calculated between all variables ( p ⩽ 0.05). To compare 505 time and COD deficit, z-scores were calculated; the difference in these scores was evaluated for each subject. The COD deficit correlated to 505 ( r = 0.74–0.81) but not sprint time ( r = −0.11 to 0.10). In contrast, 505 time did correlate with sprint time ( r = 0.52–0.70). Five of 17 subjects were classified differently for COD ability when comparing standardized scores for 505 time vs. COD deficit. Most subjects (88–94%) had a meaningful difference between 505 time and COD deficit. Using 505 time to determine COD ability may result in a large amount of replication to linear speed assessments. The COD deficit may be a practical tool to better isolate and identify an athlete's ability to change direction.